Comparison of the use of pupil diameter and galvanic skin response signals for affective assessment of computer users - Ren, Peng; Barreto, Armando; Gao, Ying; Adjouadi, Malek (Biomedical sciences instrumentation, 2012)
The implementation of Affective Computing concepts requires the assessment of the affective states in the computer user, e.g., relaxation or stress. Traditionally, the Galvanic Skin Response (GSR) signal has been analyzed as the leading indicator of the sympathetic activation that accompanies stress, when it is experienced by a computer user. However, recent research has found that the Pupil Diameter (PD), which is also controlled by the Autonomic Nervous System (ANS), can be an important indicator of sympathetic activation. This paper describes techniques for the processing of the Pupil Diameter (PD) signal to detect episodes of mental stress induced in experimental subjects, differentiating them from relaxation intervals. Our experiments also recorded and analyzed the GSR signal from the subjects, for comparison purposes. The PD signal is first pre-processed applying wavelet denoising and Kalman filtering to remove the high-frequency variations of the raw PD signal that are not representative of the subjects affective state. Then 3 features are extracted from the normalized, pre-processed PD signal and five different classification algorithms are applied on these features to differentiate the states of relaxation vs. stress in the computer user. Similarly, 3 GSR features were obtained and used for classification. PD-based classification achieved an average accuracy of 85.86%. GSR-based classification achieved an average accuracy of 60.66%. Therefore, the results indicate that the pupil diameter may be one of the most significant physiological signals to monitor for affective assessment and differentiation of relaxation vs. stress states of a computer user.